Studi kasus management pembinaan sepak bola pada club ps. Bintang kejora masbagik 2024 - Nazalussuluki Uhrowi; Herman Syah; Ali Imran (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This research aims to examine the management and coaching system implemented by the PS. Bintang Kejora Masbagik Football Club. The study applies a descriptive quantitative method by collecting data through observation, interviews, documentation, and questionnaires. The sample includes 33 respondents consisting of club management, coaches, players, and supporters. The results show that the club's management has effectively carried out the functions of planning, organizing, executing, and supervising. The coaching model is structured and follows a pyramid system, although some challenges remain regarding training facilities and financial support. The club's performance has declined in recent years, but enthusiasm to restore its former glory remains high. This research is expected to serve as a reference for improving and developing football management at the local club level.